Exploring health outcome disparities in African regional economics communities: a multilevel linear mixed-effect analysis - Ariane Ephemia Ndzignat Mouteyica; Nicholas Ngepah (BMC Public Health)
Abstract Background In African Regional Economic Communities (RECs), notable and enduring disparities exist in health outcomes. This study investigates the impact of macro-level characteristics of countries on health outcomes disparities within the African Regional Economic groupings. The study used panel data from the World Bank Development Indicators (WDI) and the Worldwide Governance Indicators (WGI), spanning 37 African countries, grouped into eight RECs between 2000 and 2019. We employed infant and under-five mortality rates and life expectancy at birth as indicators of health outcomes. Method The study used a multilevel linear (ML) mixed-effect approach to examine the influence of country-level factors on health outcome disparities within the eight African RECs recognized by the African Union. Results The findings show that higher unemployment rates and HIV incidence exacerbate these disparities, while a growing elderly population and improved access to basic drinking water can mitigate them. Increased internet usage correlates with higher within-regional inequalities in child mortality rates but reduces disparities in life expectant at birth. Urbanization trends contribute to lower-intra-regional inequality in infant mortality rates and life expectancy at birth. Higher domestic government health expenditure as a share of general government spending is linked to reduced disparities in under-five and infant mortality rates. Still, it increases inequalities in life expectancy at birth within the regional groupings. Moreover, a higher proportion of the population below 15 years old and trade gains positively influence regional disparities in life expectancy. Conversely, DTP immunization coverage among children aged 12–23 months is associated with higher within-regional inequality in infant mortality rates. Conclusions Polices aimed at reducing unemployment rates and HIV incidence should be prioritized. In addition, governments should invest in elderly care programs and infrastructure development for water supply. Efforts to promote internet access should be complemented by interventions to enhance child health and healthcare accessibility. Encouraging urban planning policies that prioritize developing healthcare infrastructure and facilitating healthcare access in urban areas is crucial. Furthermore, Governments should increase their health expenditure allocation in general government spending. Promoting strategies to enhance healthcare access and quality for specific demographics, alongside leveraging trade gains to invest in healthcare infrastructure and services, is imperative. Targeted interventions ensuring equitable access to immunization services should also be emphasized.